Invisible in the smart city: Using participatory design methods for age-friendly solutions - van Leeuwen, Cora; Devis Clavijo, Juanita; Mariën, Ilse; Jacobs, An (Frontiers in Sustainable Cities, 2022)
Older adults face unique challenges and have differing needs when navigating the urban environment. At the same time, civil servants and policymakers in cities are facing difficulties in promoting age-friendly initiatives due to the lack of knowledge, data, and tools about and for older adults. In this context, smart cities can play a key role in increasing the participation of older adults (i.e., 65 years and older) by collecting the data needed to provide knowledge of and design tools for older adults. However, using smart city data to inform policy making is made more difficult by several existing issues such as aggregated nonage-specific big data, lack of data altogether, and a disparity in access and use of digital technology. This paper endeavors to provide a methodology to ensure that the older adults are represented in the collected data and the translation of this data into automatic policy-making decisions. The Participation for Policy for Older Adults (PAR4POA) method introduces older adults' perspectives from the start of the project and its iterative approach means that older adults will share their needs and values with policymakers at different stages of a project. The use of this method enabled the co-creation of smart city solutions targeted to address the needs of older citizens in the context of 3 European regions. The PAR4POA method is specifically altered for the situation of older adults but could easily be used to include other marginalized populations. Ensuring participation in the automatic policy-making arena will empower marginalized populations and provide representation in data previously not provided.